DEVELOPING THE CREATIVE POTENTIAL OF STUDENTS IN LINGUISTIC SPECIALTIES THROUGH PROJECT ACTIVITIES - Lagay Elena Alexandrovna (American Journals Publishing, 2025)
The article considers the need for innovative changes in the professional training of philological students. One of the possible options for implementing the project method in the process of teaching the courses «Russian Orthology» and "Culture of Speech" is presented. The use of this innovative pedagogical technology ensures the development of students' independence and creative activity.
Keywords: Higher education; culture of speech, independent work. innovative technologies; project method.